2011
DOI: 10.3109/13816810.2011.628358
|View full text |Cite
|
Sign up to set email alerts
|

Disruption in Bruch membrane in patients with Stargardt disease

Abstract: Purpose To describe the spectral domain-optical coherence tomography (SD-OCT) findings of two patients with complete defects in the retinal pigment epithelium (RPE) with disruptions in Bruch membrane in Stargardt disease (STGD1). Methods Two patients with STGD1 were referred to our clinic for further evaluation. Fundus autofluorescence (FAF), spectral domain optical coherence tomography (SD-OCT), electroretinography (ERG) and Microperimetry (MP-1) were performed to assess the retinal anatomy and function. Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Such a BM defect was accompanied by a localized deep scleral staphyloma, if the BM defect was located at the posterior pole. Our report extends the list of causes for secondary BM defects and includes toxoplasmotic-like retino-choroidal scars in addition to high axial myopia, Stargardt disease (Park et al 2012) and pseudoxanthoma elasticum (Spaide & Jonas 2015) as causes for BM defects. Our report also showed that a secondary BM at the posterior pole defect can be associated with a pronounced scleral staphyloma.…”
Section: Referencessupporting
confidence: 56%
“…Such a BM defect was accompanied by a localized deep scleral staphyloma, if the BM defect was located at the posterior pole. Our report extends the list of causes for secondary BM defects and includes toxoplasmotic-like retino-choroidal scars in addition to high axial myopia, Stargardt disease (Park et al 2012) and pseudoxanthoma elasticum (Spaide & Jonas 2015) as causes for BM defects. Our report also showed that a secondary BM at the posterior pole defect can be associated with a pronounced scleral staphyloma.…”
Section: Referencessupporting
confidence: 56%
“…53 We found Bruch's membrane loss in the fovea using histology and cryosectioning methods. The ultrastructural analysis of the STGD donor identified increased thickening of Bruch's membrane, particularly in the central elastin lamina.…”
Section: Discussionmentioning
confidence: 99%
“…present. [15][16][17][18][19] Bruch's membrane is a 2-4 mm thick acellular matrix between the RPE and choroid. 20 Since clinical OCT instruments typically provide axial resolutions 5-10 mm, accurate segmentation of Bruch's membrane under normal conditions is still challenging.…”
Section: Impact Statementmentioning
confidence: 99%